2019
DOI: 10.3390/app9142835
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Variation/Response Space Complexity and Variable Completeness on BP-ANN Model Establishment: Case Study of Steel Ladle Lining

Abstract: Artificial neural network (ANN) is widely applied as a predictive tool to solve complex problems. The performance of an ANN model is significantly affected by the applied architectural parameters such as the node number in a hidden layer, which is largely determined by the complexity of cases, the quality of the dataset, and the sufficiency of variables. In the present study, the impact of variation/response space complexity and variable completeness on backpropagation (BP) ANN model establishment was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In particular, this type of modeling can be divided into two classes: hybrids, also known as gray-box modeling, which start from the premise that information inherent to the process derived from physical modeling can provide important gains to the model and, therefore, should be used to compose the solution to the problem (Tian et al, 2008;Ahmad et al, 2014;He et al, 2014;Botnikov et al, 2019;Song et al, 2019); and non-hybrids, called blackbox modeling, in which little or no prior knowledge of the system is needed. In general, this type of modeling is composed of algorithms based purely on machine learning, capable of identifying patterns between information and then predicting and executing tasks (Laha et al, 2015;Klanke et al, 2017;Wang et al, 2018;Hou et al, 2019;Jo et al, 2019).…”
Section: Types Of Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, this type of modeling can be divided into two classes: hybrids, also known as gray-box modeling, which start from the premise that information inherent to the process derived from physical modeling can provide important gains to the model and, therefore, should be used to compose the solution to the problem (Tian et al, 2008;Ahmad et al, 2014;He et al, 2014;Botnikov et al, 2019;Song et al, 2019); and non-hybrids, called blackbox modeling, in which little or no prior knowledge of the system is needed. In general, this type of modeling is composed of algorithms based purely on machine learning, capable of identifying patterns between information and then predicting and executing tasks (Laha et al, 2015;Klanke et al, 2017;Wang et al, 2018;Hou et al, 2019;Jo et al, 2019).…”
Section: Types Of Modelingmentioning
confidence: 99%
“…The results of the application revealed that the models presented considerable precision in the prediction and are satisfactory for the practical production process. Hou et al (2019) applied a BPNN to predict the thermal and thermomechanical responses of a steel ladle, consider-ing variables related to the properties of refractory linings and ladle geometry. To this end, five orthogonal matrices were used for finite element simulations and training of the neural model, with the aim of organizing the combination of ten characteristics in the variables space.…”
Section: Gray-box Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…With the use of selected supervised techniques it is possible to predict the wear rate of refractories installed in heat devices and its parameters. [28][29][30][31] Unsupervised techniques are also used when it is necessary to find comparable groups of data in large data sets. 32 The aim of this work is to apply unsupervised machine learning algorithms to identify MgO-C materials of optimal quality considering basic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Selection of such materials may be done with the use of statistical tools and machine learning techniques which are used widely in a field of refractory materials applications. With the use of selected supervised techniques it is possible to predict the wear rate of refractories installed in heat devices and its parameters 28–31 . Unsupervised techniques are also used when it is necessary to find comparable groups of data in large data sets 32 …”
Section: Introductionmentioning
confidence: 99%